Message: It is not Permissible to Selling one Animal for Another Animal with Delay Edwhile Payment, Muhammad Akmal Al-Din Al-Babarti, who died in 786 Ah, - Studying and Verification- - Asham , Ammar (Islamic Sciences Journal, 2023)
The research in your hands is a verification and a study of a message in the Hanafi jurisprudence of the sign Akmal Al-Din Baparti, entitled: (Message: It is not permissible to Selling one animal for another animal with delay edwhile payment). It is an important doctrinal issue that often occurs, especially in livestock-raising areas, The research includes of two main sections, The first of which includes a translation of the author and his mission, and a statement of the work of the researcher in the verification. The second is dedicated to the verified text . The researcher obtained through this study the following results, perhaps the most important are : • The modesty of the Babarti, and how he invested his relationship with the Sultan in the satisfaction of Allah . • The question of the doctrinal message had been disputed among the jurists, and some were fanatical about their opinion, and this letter was the appropriate response, as Baparti noted in the introduction.